1987
DOI: 10.1037/0022-006x.55.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol expectancies and the risk for alcoholism.

Abstract: The current study examined alcohol expectancies and drinking motives as correlates of alcohol involvement among adolescents at high and low risk for future alcoholism. Measures of alcohol expectancies, drinking motives, presumed personality risk for alcoholism, family history of alcoholism, and alcohol involvement were completed by 979 high school students. Alcohol expectancies and drinking motives were found to vary as a function of risk status. More important, the strength of the relations between alcohol ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 24 publications
(40 reference statements)
11
124
0
1
Order By: Relevance
“…The results indicated more positive expectancies regarding improved cognitive and motor skills and global positive changes, similar to studies examining expectancies in adolescents with at-risk of alcohol misuse (Mann, Chassin & Sher, 1987;Brown, Creamer & Stetson, 1987;Christiansen & Goldman, 1983). However, this study focused on social drinkers and therefore cannot be compared directly to a sample of at-risk adolescents.…”
Section: Alcohol Expectanciessupporting
confidence: 70%
“…The results indicated more positive expectancies regarding improved cognitive and motor skills and global positive changes, similar to studies examining expectancies in adolescents with at-risk of alcohol misuse (Mann, Chassin & Sher, 1987;Brown, Creamer & Stetson, 1987;Christiansen & Goldman, 1983). However, this study focused on social drinkers and therefore cannot be compared directly to a sample of at-risk adolescents.…”
Section: Alcohol Expectanciessupporting
confidence: 70%
“…Few studies have examined the relations between alcohol use and perceived risk for alcoholism-a type of distal negative expectancy. Studies on the relations between negative expectancies and alcohol use have had mixed results (Mann et al, 1987;McMahon et al, 1994;Sharkansky and Finn, 1998), perhaps because these relations are different in the long term than in the short term. Although we did not test the shortterm effects of perceived risk for alcoholism, our fi ndings with a 5-year time lag between assessments indicate inverse relations between perceived risk and drinking over time.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking to regulate negative affect (e.g., tension reduction) robustly predicts alcohol use and problems (Cooper, Frone, Russell, & Mudar, 1995;Mann, Chassin, & Sher, 1987). In the only study to examine the association between reasons for drinking and course of alcohol involvement, Bennett et al (1999) showed that persistent and developmentally limited courses of drinking tended to have the highest escape and enhance reasons for use, followed by moderate (and low) groups.…”
Section: Reasons For Drinkingmentioning
confidence: 99%